2014
DOI: 10.1128/aem.03151-13
|View full text |Cite
|
Sign up to set email alerts
|

Establishing the Yeast Kluyveromyces lactis as an Expression Host for Production of the Saposin-Like Domain of the Aspartic Protease Cirsin

Abstract: Typical plant aspartic protease zymogens comprise a characteristic and plant-specific insert (PSI). PSI domains can interact with membranes, and a role as a defensive weapon against pathogens has been proposed. However, the potential of PSIs as antimicrobial agents has not been fully investigated and explored yet due to problems in producing sufficient amounts of these domains in bacteria. Here, we report the development of an expression platform for the production of the PSI domain of cirsin in the generally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 33 publications
0
5
0
1
Order By: Relevance
“…This ability is closely related to its antimicrobial activity: a study with Solanum tuberosum aspartic proteinase PSI showed that it enhances Arabidopsis thaliana resistance against Botrytis cinerea infection [24], and another report using the same PSI showed that it is cytotoxic against Gram-negative and Gram-positive bacteria [25]. All these particular features have raised the interest in this domain and several studies were conducted using PSIs isolated from different plant species in an attempt to better characterize this domain, considered to be “an enzyme inside an enzyme” [24,25,26,27,28].…”
Section: Introductionmentioning
confidence: 99%
“…This ability is closely related to its antimicrobial activity: a study with Solanum tuberosum aspartic proteinase PSI showed that it enhances Arabidopsis thaliana resistance against Botrytis cinerea infection [24], and another report using the same PSI showed that it is cytotoxic against Gram-negative and Gram-positive bacteria [25]. All these particular features have raised the interest in this domain and several studies were conducted using PSIs isolated from different plant species in an attempt to better characterize this domain, considered to be “an enzyme inside an enzyme” [24,25,26,27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Recently Curto et al. has also reported the expression of glycosylated and non‐glycosylated heterologous proteins in K. lactis and they had employed the same strategy for purification of the protein forms. It was also demonstrated that the His tag could be removed easily by treatment with a Tobacco Etch Virus (TEV) protease.…”
Section: Discussionmentioning
confidence: 99%
“…32 An alternative yeast expression organism for the production of AMPs is Kluyveromyces lactis (K. lactis) which has been already used for the recombinant production of AMPs like the Saposin-Like Domain of the Aspartic Protease Cirsin. 33 The advantages of K. lactis such as simple genetic manipulation, the ability to use both integrative and episomal expression vectors, and the availability of a fully sequenced genome made it an attractive alternative to P. pastoris. 34 Especially for the production of peptides derived from higher eukaryotes like fish or mammalians, the use of mammalian cell lines can be favorable due to correct folding and post-translational without further genetic modifications of the used organism.…”
Section: Other Expression Systems For Amp Productionmentioning
confidence: 99%
“…An alternative yeast expression organism for the production of AMPs is Kluyveromyces lactis ( K. lactis ) which has been already used for the recombinant production of AMPs like the Saposin‐Like Domain of the Aspartic Protease Cirsin . The advantages of K. lactis such as simple genetic manipulation, the ability to use both integrative and episomal expression vectors, and the availability of a fully sequenced genome made it an attractive alternative to P. pastoris …”
Section: Heterologous Expression Hosts For Insect‐derived Ampsmentioning
confidence: 99%